Soil characteristics and CO2 emissions of ex-burnt peatland in Kubu Raya District, West Kalimantan, Indonesia - Dwi Astiani; TRI WIDIASTUTI; SITI LATIFAH; DARBIN SIMATUPANG (Society for Indonesian Biodiversity, 2020)
Abstract. Astiani D, Widiastuti T, Latifah S, Simatupang D. 2020. Soil characteristics and CO2 emissions of ex-burnt peatland in Kubu Raya District, West Kalimantan, Indonesia. Biodiversitas 21: 3691-3698. West Kalimantan, Indonesia has a large extent of tropical peatland with total ??1.74 million ha with only 44.5% of such areas remaining as peat forest, while the rests have been converted into plantations, agricultural lands, and shrubs. The conversion of peat forest often uses fires to clear the vegetation and is followed by building canal to drain the water. The lack of vegetation combined with drought soil trigger uncontrolled escaped fire, especially in the dry season or El-Nino events, which is likely to affect soil characteristics and emit carbon dioxide. The purpose of this study is to examine the changes in soil characteristics both physical and chemical properties and to investigate CO2 emissions from peat soil post-fire. As a comparison, similar parameters were also assessed in non-burnt sites. The results showed significant differences in some peat soil characters both physically and chemically between ex-burnt and non-burnt peatland. The ex-burnt site had higher pH, available phosphorus and C/N ratio than those in the non-burnt site. Conversely, the total nitrogen and carbon contents, and cation exchange capacity were lower which is likely due to leaching. Peat fires also impacted physical characteristics of the soil such as increasing soil bulk density, reducing soil water content, soil temperature, especially in wet conditions. Carbon dioxide emissions in the ex-burnt site were considered higher than non-burnt site. These results could be brought out as a part of baseline data in managing ex-burnt peatlands to maintain a balance between carbon output and input and efforts on preventing peatland fires from becoming continuous carbon sources.